The Determination of Psilocin and Psilocybin in Hallucinogenic Mushrooms by HPLC Utilizing a Dual Reagent Acidic Potassium Permanganate and Tris(2,2'-bipyridyl)ruthenium(II) Chemiluminescence Detection System - Anastos, N.; Lewis, Simon; Barnett, N.; Sims, D. (Blackwell Publishing, 2006)
This paper describes a procedure for the determination of psilocin and psilocybin in mushroom extracts using high-performance liquid chromatography with postcolumn chemiluminescence detection. A number of extraction methods for psilocin and psilocybin in hallucinogenic mushrooms were investigated, with a simple methanolic extraction being found to be most effective. Psilocin and psilocybin were extracted from a variety of hallucinogenic mushrooms using methanol. The analytes were separated on a C12 column using a (95:5% v/v) methanol: 10mM ammonium formate, pH 3.5 mobile phase with a run time of 5 min. Detection was realized through a dual reagent chemiluminescence detection system of acidic potassium permanganate and tris(2,20-bipyridyl)ruthenium(II). The chemiluminescence detection system gave improved detectability when compared with UV absorption at 269 nm, with detection limits of 1.2 x 10-8 and 3.5 x 10-9 mol/L being obtained for psilocin and psilocybin, respectively. The procedure was applied to the determination of psilocin and psilocybin in three Australian species of hallucinogenic mushroom.